Burnout, psychopathology and purpose in life in healthcare workers during COVID-19 pandemic - O'Higgins, Marcelo; Rojas, Luz Angela; Echeverria, Iván; Roselló-Jiménez, Lorena; Benito, Ana; Haro, Gonzalo (Frontiers in Public Health, 2022)
Background The COVID-19 pandemic has led to a significant increase in the workload of healthcare workers that, together with the risks associated with exposure to this new virus, has affected their mental health. Objectives The objective of the current study was to determine the prevalence of psychopathology and burnout syndrome in healthcare workers and the predictive role of purpose in life and moral courage in this relationship. Methods A cross-sectional study was carried out in 115 Spanish healthcare workers. Results Participants with burnout had higher anxiety (p = 0.001), depression (p < 0.001), post-traumatic stress (p = 0.01) and alcohol consumption (p = 0.03) levels. The different components of burnout (emotional fatigue and despersonalization) were associated with the occurrence of anxiety (OR = 0.31) and depression (OR = 0.26), respectively. A strong purpose in life decreased emotional fatigue (OR = −0.39) depersonalization (OR = −0.23) scores, increased personal accomplishment (OR = 0.52), subsequently reducing burnout levels (OR = −0.45). Conclusions Purpose in life was most strongly related to decreased levels of burnout. Furthermore, an association between anxiety, depression and the components of burnout was found.